Latent Heat Storage with Phase Change Materials (PCMs) - Zhang, H. L.; Baeyens, J.; Degrève, J.; Pitié, F. (Journal of Technology Innovations in Renewable Energy, 2013)
Latent heat thermal energy storage with phase change materials (PCMs) is attractive since providing a high energy density storage due to the phase change by solidification/melting at constant temperature. Relative to sensible heat energy storage systems, latent heat storage with PCMs requires a smaller weight and volume of material for a given amount of captured/stored energy, and has the capacity to store heat of fusion at a constant or nearly constant temperature, thus maintaining a high and constant temperature difference between the heat exchanging surface and the PCMs. The present review paper will summarize the required properties of PCMs, with their respective advantages and disadvantages; the current state of development and manufacturing; the development of PCM applications, including their incorporation into heat exchangers, insertion of a metal matrix into the PCM, the use of PCM dispersed with high conductivity particles. PCM uses will be illustrated through some case-studies.